2008
DOI: 10.1002/sia.2965
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial metal implant with a TiO2‐conferred photocatalytic bactericidal effect against Staphylococcus aureus

Abstract: Photocatalysis with anatase Titanium dioxide (TiO 2 ) under ultraviolet A (UVA) has a well recognized bactericidal effect. There have been a few reports, however, on the effects of photocatalysis on bio-implant-related infections. The purpose of present study was to evaluate the photocatalytic bactericidal effects of anatase TiO 2 on Staphylococcus aureus (S. aureus) associated with surgical site infections.TiO 2 films were synthesized on commercially pure titanium substrates and SUS316 stainless steel using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 49 publications
(23 reference statements)
1
49
1
Order By: Relevance
“…Negative pulses of 20 kV having a duration of 50 µs and a repetition rate of 100 Hz gave TiO 2 films with a thickness of 318 nm after annealing at temperatures between 673 K and 1023 K for 1 h. Similar results were obtained by Jing et al (110). Shiraishi et al (111) described the preparation of antibacterial metal implant (titanium and SUS316 stainless steel) with a TiO 2 using a plasma source ion implantation followed by annealing. The TiO 2 layer conferred photocatalytic bactericidal effect against S. aureus under UVA irradiation.…”
Section: Anodic Oxidationsupporting
confidence: 66%
“…Negative pulses of 20 kV having a duration of 50 µs and a repetition rate of 100 Hz gave TiO 2 films with a thickness of 318 nm after annealing at temperatures between 673 K and 1023 K for 1 h. Similar results were obtained by Jing et al (110). Shiraishi et al (111) described the preparation of antibacterial metal implant (titanium and SUS316 stainless steel) with a TiO 2 using a plasma source ion implantation followed by annealing. The TiO 2 layer conferred photocatalytic bactericidal effect against S. aureus under UVA irradiation.…”
Section: Anodic Oxidationsupporting
confidence: 66%
“…Systems penetrating soft tissue, such as bone anchored prostheses or dental implants, are particularly susceptible to infection due to high exposure to bacteria from the environment, and the application of antibiotics for combatting these infections in such cases may not be sufficient [11,32]. Reducing the general use of antibiotics to treat infection has also been a long standing call to limit bacterial resistance [33].…”
Section: Discussionmentioning
confidence: 99%
“…In applying the photocatalytic bactericidal properties of titania, an on-demand feature for decontamination can be added to biomedical surfaces, and is of particular interest for percutaneous implants and devices. A number of studies have been devoted to this matter and have shown promising results [4,11,[34][35][36][37], but further research is needed to improve efficiency and avoid adverse effects of UV light on healthy tissue, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Titania and TiO 2 based semiconductors are of a considerable interest as catalysts, sensors, implants, medical media, corrosion protectors and electronic components widely studied and used in a variety of physicochemical, biological and industrial processes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Introducing dopants of multifarious characters (metals, nonmetals) [16][17][18][19][20][21][22] involves the band gap narrowing of titania materials which gives rise to energy saving for diverse technological purposes.…”
Section: Introductionmentioning
confidence: 99%